Reforming governance through policy instruments: how and to what extent standards, tests and accountability in education spread worldwide. Issue 2 (4th March 2019) - Verger, Antoni; Fontdevila, Clara; Parcerisa, Lluís
ABSTRACT: In the last decades, most countries have adopted data-intensive policy instruments aimed at modernizing the governance of education systems, and strengthening their competitiveness. Instruments such as national large-scale assessments and test-based accountabilities have disseminated widely, to the point that they are being enacted in countries with very different administrative traditions and levels of economic development. Nonetheless, comparative research on the trajectories that governance instruments follow in different institutional and socio-economic contexts is still scarce. On the basis of a systematic literature review ( n  = 158), this paper enquires into the scope and modalities of educational governance change that national large-scale assessments and test-based accountability instruments have triggered in a broad range of institutional settings. The paper shows that, internationally, educational governance reforms advance through path-dependent and contingent processes of policy instrumentation that are markedly conditioned by prevailing politico-administrative regimes. The paper also reflects on the additive and evolving nature of educational governance reforms.